Wòlak-waliké jaman; Exploring contemporary Walikan in public space - Yannuar, Nurenzia (Wacana, Journal of the Humanities of Indonesia, 2018)
This article describes the current use of Walikan, a youth language in Malang, Indonesia. Unlike any previously described youth registers in Indonesia, Walikan has been around since as early as the 1940s and has continuously reinvented itself ever since. As will be shown, the speakers of Walikan have certain strategies to keep the practice alive. In addition to the use of Walikan in face-to-face communication, they also use Walikan in songs, local TV news, local newspaper columns as well as in public signs. The analysis focuses on how a youth language which began as an oral practice has been maintained through written and audio-visual media offline and online. The results inform us how a community can work together to shape its identity through linguistic means.